Productivity of Comet Goldfish (Carassius auratus) Culture in Aquaponics System Using Fine Bubbles (FBs) - Yuli - Andriani (Aceh Journal of Animal Science, 2023)
Oxygen is an important factor in the process of fish farming. This study aims to determine the application of FBs pressure that can increase the productivity of comet goldfish farming in an aquaponic system. The research was carried out from January to March 2022 at the Ciparanje Green House, Faculty of Fisheries and Marine Sciences, Padjadjaran University, Jatinangor. This study used a completely randomized design (CRD) experimental method with four treatments and three replications. The treatment used was the application of FBs pressure of 0 atm (A), 5.25 atm (B), 5.5 atm (C), and 5.75 atm (D). Maintenance of test fish for 30 days with ad satiation feeding. Observation of fish growth through sampling is done by taking fish 10% of the total population randomly in each pond. Data were analyzed using the F test at a 95% confidence level, followed by Duncan's multiple range test with a 95% confidence level, while water quality data were analyzed descriptively. The results showed that the specific daily growth rate of FBs 5.75 was 2.51%, the absolute length growth was 3.33%, the absolute weight growth was 1.70 grams and the fish survival rate was 99.3%.